The Alignment of Objectives Towards Benefits Perceived by Users and Empirical Impacts in The Implementation of E- Performance within Government Organizations - Pratama, Azmi; Susanto, Tony Dwi (IPTEK Journal of Proceedings Series, 2020)
Nowadays, E-government plays a very crucial role in the country. E-government is expected to have an impact in changing work culture to be more efficient so that it is free from non-transparency and behaviour of corruption, collusion, and nepotism. One application that is used in the scope of E-government is called E-Performance. E-Performance is implemented with the aim to enhance civil servants’ performance and to accommodate the reward and punishment system. The implementation of E-Performance in Indonesia has become a phenomenon. It can be seen from the amount of organization that has started implementing the application. Previous research conducted on E-Performance emphasized on the technical and matters relating to users and the resulting impact. The impact and benefits felt by users and organizations in the implementation of an application must be aligned with the initial objectives made by the policy makers. The results of the study are a proven model. Furthermore, it revealed some new facts related to the alignment of the objectives of E-Performance implementation with the benefits perceived by the users and also the empirical impact on government organizations. The results of this study can be used to help the government in planning, implementing, and improving the implementation of E-Performance.